2017
DOI: 10.1186/s12910-017-0210-0
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues of informed consent in malaria research proposals submitted to a research ethics committee in Thailand: a retrospective document review

Abstract: BackgroundThe informed-consent process should be one of meaningful information exchange between researchers and study participants. One of the responsibilities of research ethics committees is to oversee appropriate informed consent. The committee must consider various matters before deciding whether the process is appropriate, including the adequacy and completeness of the written information provided to study participants, and the process of obtaining informed consent.This study aimed to identify, quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(41 reference statements)
2
0
0
1
Order By: Relevance
“…This article addressed a basic descriptive question-"what are the ethical issues raised by RECs reviewing biomedical research in South Africa?" The most frequent ethical issue identified in our study was informed consent-a finding comparable with similar studies in South Africa (Clarke, 2014;Cleaton-Jones, 2010;Tsoka-Gwegweni & Wassenaar, 2014), the United Kingdom (Angell, Bryman, Ashcroft, & Dixon-Woods, 2008;Boyce, 2002), the United States (Lidz et al, 2012), Thailand (Adams et al, 2017), the Netherlands (van Lent, Rongen & Out, 2014), France (Decullier, Lhéritier, & Chapuis, 2005), Brazil (Bueno et al, 2009), Spain (Dal-Ré, Morejón & Ortega, 2004; Martín-Arrabis, Rodríguez-Lozano, & Arias-Díaz, 2012), and Finland (Hemminki, Virtanen, & Regushevskaya, 2015). A German study reported that of 1,299 queries, 53% concerned the patient information and consent document (Russ, Busta, Riedel, Zollner, & Jost, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…This article addressed a basic descriptive question-"what are the ethical issues raised by RECs reviewing biomedical research in South Africa?" The most frequent ethical issue identified in our study was informed consent-a finding comparable with similar studies in South Africa (Clarke, 2014;Cleaton-Jones, 2010;Tsoka-Gwegweni & Wassenaar, 2014), the United Kingdom (Angell, Bryman, Ashcroft, & Dixon-Woods, 2008;Boyce, 2002), the United States (Lidz et al, 2012), Thailand (Adams et al, 2017), the Netherlands (van Lent, Rongen & Out, 2014), France (Decullier, Lhéritier, & Chapuis, 2005), Brazil (Bueno et al, 2009), Spain (Dal-Ré, Morejón & Ortega, 2004; Martín-Arrabis, Rodríguez-Lozano, & Arias-Díaz, 2012), and Finland (Hemminki, Virtanen, & Regushevskaya, 2015). A German study reported that of 1,299 queries, 53% concerned the patient information and consent document (Russ, Busta, Riedel, Zollner, & Jost, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…At least 20% of the submitted ICFs during the postintervention period had deficient components for information about the research contact team, study duration, travel compensation, adequate description of research procedure, and use of technical terms. These findings were consistent with those reported in previous studies and likely reflect inadequate investigator knowledge of research methods and ethics considerations necessary for study protocols and ICF (Adams et al, 2017;Bergstraesser et al, 2020;Shah et al, 2016;Shetty et al, 2012;van Lent et al, 2014). Regular REC audits to periodically identify these deficiencies and tailored trainings for investigators with repeated resubmission requirements seem prudent.…”
Section: Discussionsupporting
confidence: 87%
“…Hay que considerar entonces, que la cuestión basal en todos los códigos éticos, es el principio de una decisión libre e informada (Adams et al, 2017). Bajo esta consigna, en la investigación biomédica y en la experimentación clínica, se exige a los investigadores un comportamiento ético durante el proceso del estudio, que garantice un trato con justicia y beneficencia, no maleficencia y respeto, (T. L. Beauchamp & Childress, 2001) que evidencie el reconocimiento y ejercicio de la autonomía del participante.…”
Section: Salud Y Consejo De Organizaciones Internacionales De Las Cie...unclassified